Outcome of surgical treatment of highgrade intramedullary astrocytomas - Flamerz, Bassam M. (AL-Kindy College Medical Journal, 2011)
Background: Intramedullary astrocytomas account for about 1% of all CNS tumors and 6–8% of spinal cord tumors. The vast majority of intramedullary astrocytomas are slowgrowing lesions. Objectives: The goal in this study was to review a series of patients who underwent surgical removal of intramedullary high-grade astrocytomas, focusing on the functional outcome and the effect of multimodality treatment on the survival of patients with high grade intramedullary astrocytoma. Methods: Between June 1999 and June 2004, 22 patients underwent removal of intramedullary high-grade astrocytomas in four neurosurgical hospital in Baghdad/ Iraq (Neurosurgical hospital, Al Shaheed Adnan Hospital for Surgical Speeialticsa, Nursing Home Hospital Lesions were located in the cervical segment of the spinal cord in 12 patients, and patients. Results: Histological examinations showed 10 Grade III astrocytomas and 12 glioblastomas. Only 2 of the 22 high-grade astrocytomas could be completely removed. The clinical postoperative status worsened in 14 patients (63.6%), was unchanged in seven patients (31.8%), and there was one case of intraoperative death (4.5%). None of the 22 patients showed improvement in their neurological status postoperatively. In this series, excluding the one intra-operative death, all patients died of the progression of the malignancy. Conclusions: Surgical treatment did not ameliorate the postoperative neurological status; instead, in the majority of cases, it prompted a worsening of the deficit. Radiotherapy and chemotherapy have a little influence on the length of survival. In this series, multimodality treatment of intramedullary high-grade astrocytomas has been shown to increase length of survival without improving the neurological status.